PENYELESAIAN KONFLIK DALAM RUMAH TANGGA STUDI KASUS PENYEBAB PERCERAIAN DI KOTA AMBON - Rustam Latupono; La Jamaa; Abu Bakar Kabakoran (IAIN Ambon, 2023)
The thesis examines the problem of resolving domestic conflicts in case studies of the causes of divorce in Ambon City. This study aims to find and examine more deeply about: (1) what are the factors causing the high divorce rate in Ambon City, and (2) what are the strategies for resolving marital conflict to reduce the divorce rate in Ambon City. This research is a field research (field research), using descriptive-analytical method. The type of data used in this research is qualitative. The data collection techniques are carried out by means of observation, interviews and literature. The results of the study show that: (1) the factors causing the high divorce rate in Ambon City, among others, are because married couples lack a good understanding of religion so that problems that arise in their household are difficult to overcome besides that they are always suspicious of each other, feel uncomfortable with his life partner, is not responsible for his family (abandoning the family), has another ideal woman and commits domestic violence, always quarrels in the family and is difficult to reconcile, and there is a third party. (2) The conflict resolution strategy for married couples to reduce the divorce rate in Ambon City includes: (a) prospective brides are required to attend pre-marital education through bride-to-be courses as anticipation in order to be able to resolve marital conflicts; (b) optimizing the role of hakamain (two peacemakers) on the part of the husband and wife; and (c) optimizing the cultural role of married brothers and the like to reconcile marital conflicts so that they do not result in divorce.Keywords: Household, resolution conflict, divorce.